2022
DOI: 10.1088/1741-2552/ac63e8
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the short-latency evoked response to intracortical microstimulation across a multi-electrode array

Abstract: Objective. Persons with tetraplegia can use brain-machine interfaces to make visually guided reaches with robotic arms. Without somatosensory feedback, these movements will likely be slow and imprecise, like those of persons who retain movement but have lost proprioception. Intracortical microstimulation (ICMS) has promise for providing artificial somatosensory feedback. If ICMS can mimic naturally occurring neural activity, afferent interfaces may be more informative and easier to learn than interfaces that e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 79 publications
9
27
0
Order By: Relevance
“…We observe a stereotyped, electrically-evoked spiking activity pattern -a brief excitation followed by 125.0±5.5 ms of inhibition -in local cortical neurons regardless of stimulation depth (superficial vs. deep), area (MO vs. SS), or behavioral state (quiet and active wakefulness, i.e., running, anesthetized). This pattern has been previously reported in different species (Butovas et al, 2006;Butovas & Schwarz, 2003;Chung & Ferster, 1998;Contreras & Steriade, 1995;Douglas & Martin, 1991;Grenier et al, 1998;Hao et al, 2016;Kara et al, 2002;Logothetis et al, 2010;Sombeck et al, 2022;Vyazovskiy et al, 2013) and is reminiscent of the bi-stability reported in deep sleep and in unconscious patients following a brief stimulation (Hill & Tononi, 2005;Pigorini et al, 2015;Rosanova et al, 2018;Timofeev et al, 2001;Usami et al, 2015). Other studies also described rebound excitation at similar latencies following stimulationevoked inhibitory periods (Butovas et al, 2006;Butovas & Schwarz, 2003;Grenier et al, 1998).…”
Section: Stereotyped Tri-phasic Spiking Pattern In Cortical and Thala...supporting
confidence: 84%
See 1 more Smart Citation
“…We observe a stereotyped, electrically-evoked spiking activity pattern -a brief excitation followed by 125.0±5.5 ms of inhibition -in local cortical neurons regardless of stimulation depth (superficial vs. deep), area (MO vs. SS), or behavioral state (quiet and active wakefulness, i.e., running, anesthetized). This pattern has been previously reported in different species (Butovas et al, 2006;Butovas & Schwarz, 2003;Chung & Ferster, 1998;Contreras & Steriade, 1995;Douglas & Martin, 1991;Grenier et al, 1998;Hao et al, 2016;Kara et al, 2002;Logothetis et al, 2010;Sombeck et al, 2022;Vyazovskiy et al, 2013) and is reminiscent of the bi-stability reported in deep sleep and in unconscious patients following a brief stimulation (Hill & Tononi, 2005;Pigorini et al, 2015;Rosanova et al, 2018;Timofeev et al, 2001;Usami et al, 2015). Other studies also described rebound excitation at similar latencies following stimulationevoked inhibitory periods (Butovas et al, 2006;Butovas & Schwarz, 2003;Grenier et al, 1998).…”
Section: Stereotyped Tri-phasic Spiking Pattern In Cortical and Thala...supporting
confidence: 84%
“…This allowed us to observe the LFP and spiking activity of hundreds of individual cortical and thalamic neurons. Because we inserted a Neuropixels probe near the stimulating electrode (within 0.5 mm) and, often, up to two more Neuropixels probes at distal locations, we observed direct responses (i.e., here defined operationally as neurons that spike between 2-25 ms following the electrical pulse; this might miss a handful of very rapidly responding neurons; see Sombeck et al, 2022; Stoelzel et al, 2009) and indirect responses to the electrical stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…We inserted a Neuropixels probe near the stimulating electrode (within 0.5 mm) and, often, up to two additional Neuropixels probes at distal locations. We observed direct responses (i.e., defined operationally as neurons that spike between 2-25 ms following the electrical pulse; this might miss a handful of very rapidly (i.e., < 2 ms) responding neurons; see (Sombeck et al, 2022); (Stoelzel et al, 2009)) as well as indirect responses to the electrical stimulation.…”
Section: The Spiking Response Pattern Of the Stimulated Cortex Echoes...mentioning
confidence: 99%
“…Chronic electrical microstimulation poses numerous challenges: it is invasive, can inadvertently activate neurons up to millimeters away from the stimulation site (Histed et al ., 2009), and can cause tissue degradation at the site of electrode insertion (Polikov et al ., 2005). Furthermore, simultaneous recording is complicated by a prominent stimulation artifact (Weiss et al ., 2019), and even studies with concurrent recording rarely examine the activity evoked at the stimulation site (Allison-Walker et al, 2021; Butovas and Schwarz, 2003; Chen et al, 2020; Hao et al, 2016) (but see (Sombeck et al, 2022)). Finally, electrical microstimulation cannot target genetically separable neural populations.…”
Section: Discussionmentioning
confidence: 99%